2012
DOI: 10.1021/bm301321d
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Hydrogel Has a Negative Impact on in Vitro Collagen 1 Deposition by Fibroblasts

Abstract: Hydrogels have been widely investigated as 3D culture substrates because of their reported structural similarity to the extracellular matrix (ECM). Limited ECM deposition, however, occurs within these materials, so the resulting "tissues" bear little resemblance to those found in the body. Here matrix deposition by fibroblasts encapsulated within a calcium alginate (Ca-alg) hydrogel was investigated. Although the cells transcribed mRNA for coll Iα over a period of 3 weeks, very little collagen protein depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…For poly(ethylene glycol) hydrogels, it has been shown that increasing polymer densities efficiently limit the transport of ECM molecules through the gel, resulting in strong pericellular localizations, even of the relatively small glycosaminoglycans [5]. Another study, using alginate hydrogels as immobilization matrix [28], argued differently on the issue of ECM molecule transport. They found procollagens escaping the hydrogels to the culture medium, and argued that both procollagen and BMP-1, being negatively charged, can diffuse through the gel, which is also negatively charged.…”
Section: Discussionmentioning
confidence: 99%
“…For poly(ethylene glycol) hydrogels, it has been shown that increasing polymer densities efficiently limit the transport of ECM molecules through the gel, resulting in strong pericellular localizations, even of the relatively small glycosaminoglycans [5]. Another study, using alginate hydrogels as immobilization matrix [28], argued differently on the issue of ECM molecule transport. They found procollagens escaping the hydrogels to the culture medium, and argued that both procollagen and BMP-1, being negatively charged, can diffuse through the gel, which is also negatively charged.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, this was thought to be principally a consequence of the modulus of the materials, but more recently reports have suggested that this can be modified by changing the distribution of grafted adhesion moieties and the nature of the interactions that may be formed with the polymer chain . It has become clear that the level of entrapment that can be provided by the relatively stiff quiescently gelled matrix can have a significant influence on biological properties, including the capacity of cells to proliferate, maintain specific phenotypes or even secrete functional protein molecules as shown in Figure …”
Section: The Delivery Of Biological Therapeutics Using Hydrogelsmentioning
confidence: 99%
“…It has been incorporated into collagen-based scaffolds to improve their structural stability[47]. However, alginate by itself negatively impacts collagen type one deposition from dermal fibroblasts, potentially making them a non-ideal polymer for skin substitutes[80]. Alginate has been largely considered an ideal polymer for skin printers, devices that seed skin cells onto prefabricated biodegradable scaffolds, due to its ionic cross-linking mechanism[81,82].…”
Section: Components Of a Skin Substitutementioning
confidence: 99%